Channel Capacity of the OAM-Based Free-Space Optical Communication Links With Bessel–Gauss Beams in Turbulent Ocean - Mingjian Cheng; Lixin Guo; Jiangting Li; Yixin Zhang (IEEE Photonics Journal)
An orbital angular momentum (OAM)-mode transmission model of Bessel–Gauss (BG) beams is established to derive an analytic expression of the channel information capacity of an OAM-based free-space optical (FSO) communication system with non-diffraction BG beams in weak turbulent ocean. Effects of oceanic turbulence on the channel information capacity of this communication system are discussed in detail. Numerical results show that oceanic turbulence induces an evident spread of OAM-mode transmission probability spectrum and severely affects the channel information capacity of OAM-based FSO communication systems. The influences of beam parameter $η$ of BG and dual BG beams on channel information capacity are contrary to each other. BG beams show significant advantages over Laguerre–Gaussian beams in mitigating the effects of turbulence and improving the performance of OAM-based FSO communication links. The effects of oceanic turbulence on the channel information capacity become stronger with the increase in oceanic turbulence parameter, rate of dissipation of mean-squared temperature, and temperature–salinity balance parameter, as well as with the decrease in the rate of dissipation of turbulent kinetic energy per unit mass of fluid. Choosing an optimum blue–green wavelength and increasing $η$ of the BG beam can effectively improve the performance of an OAM-based FSO communication system in turbulent ocean.